(untitled) (REMUNOM, 2026)
Inga marginata Willd. (Fabaceae), commonly known as ingá-feijão, is a native Brazilian tree species widely distributed across the country. Understanding its response to water limitation during early development is essential for seedling production and ecological restoration. This study evaluated the initial growth of I. marginata seedlings subjected to different irrigation regimes. Thirty seedlings were cultivated in 1.5-L plastic bags and assigned to three treatments according to water availability: T1, three irrigations of 200 mL plant⁻¹ day⁻¹; T2, one irrigation of 200 mL plant⁻¹ day⁻¹; and T3, one irrigation of 200 mL plant⁻¹ every 48 h. The experiment lasted 30 days, during which height, stem base diameter, and number of leaves were measured to calculate absolute growth. At harvest, dry biomass was determined and seedling quality was assessed using the Dickson Quality Index. Seedlings irrigated daily (T1 and T2) showed greater height increment and leaf dry mass than those irrigated every 48 h (T3). No mortality was observed in any treatment. The results indicate that I. marginata seedlings exhibit initial tolerance to moderate water deficit, partly through reductions in leaf production, which is relevant for nursery management and restoration programs.